Intergenerational Mobility How Gender, Race, and Family Structure Affect Adult Outcomes - Kimmel, Jean (W.E. Upjohn Institute, 2021)
This volume presents a complex portrait of the interrelationships among parents' marital status and education, child gender, and the nature and success of children's transitions into adulthood. The first three chapters focus on differences in parents' investments in their children, while the final three chapters focus directly on intergenerational income mobility.